Leadership and Organizational Behavior Training for Student Organizations at Universiti Malaysia Terengganu (UMT) - Sri Rahmayanti; Ayuda, Fitrien; Ramadhan, Rian Rahmat; Misral, Misral; Bakaruddin, Bakaruddin; Perdana, Riky; Hastuti, Dwi (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2025)
Pengabdian masyarakat internasional ini bertujuan untuk meningkatkan kapasitas kepemimpinan dan pemahaman perilaku organisasi mahasiswa Universiti Malaysia Terengganu (UMT) melalui pelatihan Leadership and Organizational Behavior. Mahasiswa merupakan aset sumber daya manusia strategis yang berperan sebagai agen perubahan di lingkungan kampus dan masyarakat. Namun, berbagai organisasi mahasiswa masih menghadapi tantangan berupa lemahnya kepemimpinan efektif, rendahnya kualitas komunikasi, serta konflik internal organisasi.Kegiatan pengabdian ini dilaksanakan melalui pendekatan pelatihan partisipatif, diskusi kelompok, simulasi, dan studi kasus organisasi mahasiswa. Peserta kegiatan terdiri dari pengurus dan anggota aktif organisasi mahasiswa UMT. Evaluasi dilakukan menggunakan metode pre-test dan post-test, observasi partisipasi, serta kuesioner kepuasan peserta. Hasil kegiatan menunjukkan adanya peningkatan signifikan pada pemahaman konsep kepemimpinan, perilaku individu dan kelompok, serta kemampuan kerja tim dan manajemen konflik. Kegiatan ini memberikan kontribusi praktis dalam pengembangan SDM mahasiswa dan memperkuat kolaborasi pengabdian masyarakat internasional Indonesia–Malaysia.AbstractThis international community service aims to improve the leadership capacity and understanding of organisational behaviour of students at Universiti Malaysia Terengganu (UMT) through Leadership and Organisational Behaviour training. Students are strategic human resources assets who act as agents of change on campus and in the community. However, various student organisations still face challenges in the form of weak effective leadership, poor communication quality, and internal organisational conflicts.This community service activity was carried out through participatory training, group discussions, simulations, and case studies of student organisations. Participants consisted of administrators and active members of UMT student organisations. Evaluation was conducted using pre-test and post-test methods, participation observation, and participant satisfaction questionnaires. The results of the activity showed a significant increase in understanding of leadership concepts, individual and group behaviour, as well as teamwork and conflict management skills. This activity made a practical contribution to the development of student human resources and strengthened Indonesia-Malaysia international community service collaboration.Keywords: leadership, organisational behaviour, international community service, student organisations, human resource development